2020
DOI: 10.1016/j.psj.2020.06.059
|View full text |Cite
|
Sign up to set email alerts
|

In vivo collagen and mixed muscle protein turnover in 2 meat-type broiler strains in relation to woody breast myopathy

Abstract: Two meat-type broiler strains, strain A and strain B, were reared in floor pens (25 birds/pen; 45 pens/strain) for pectoralis (P) major collagen and mixed muscle protein turnover ( PT ) study from 0–56 D using primary breeder nutrition and husbandry guidelines. Forty broilers (n = 10/strain for collagen PT; n = 10/strain for mixed muscle PT) were selected at each sampling age at day 21, 28, 35, 42, and 56 and infused with 1- 13 C proline ( Pro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Genes related to deubiquitinases such as ubiquitin-specific proteases are expressed higher with myopathy broiler at d 21 and d 42 (OTUD1 and SACS, respectively) that play role in steady state availability of monoubiquitin and regulation of substrate degradation at the proteasome ( Reyes-Turcu et al., 2009 ). Earlier studies also reported the higher mixed muscle degradation rates in myopathy broiler compared to non-myopathy ( Maharjan et al., 2020c ), the potential phenomenon responsible for leaving the space for connective tissue growth and lipid deposition when WB myopathy is concurrently occurring with white striping of muscle (Kuttappan et al., 2016; Vignale et al., 2017 ).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Genes related to deubiquitinases such as ubiquitin-specific proteases are expressed higher with myopathy broiler at d 21 and d 42 (OTUD1 and SACS, respectively) that play role in steady state availability of monoubiquitin and regulation of substrate degradation at the proteasome ( Reyes-Turcu et al., 2009 ). Earlier studies also reported the higher mixed muscle degradation rates in myopathy broiler compared to non-myopathy ( Maharjan et al., 2020c ), the potential phenomenon responsible for leaving the space for connective tissue growth and lipid deposition when WB myopathy is concurrently occurring with white striping of muscle (Kuttappan et al., 2016; Vignale et al., 2017 ).…”
Section: Discussionmentioning
confidence: 91%
“…Studies on metabolic and physiological findings have showed the higher in-vivo muscle degradation rates occurred in myopathy broiler compared to non-myopathy ( Abasht et al., 2016 ; Maharjan et al., 2019 ; Maharjan et al., 2020c ). The higher degradation of mixed muscle proteins occurred in the P. major could be further complemented by significant higher expression of genes related to oxidative stress (BTG2, ZNF236, CXCR4, HMOX1) and hypertensive effects (ZNF236 and UTS2R) in the WB affected muscle as found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations